Heavy equipment business model based on lifetime value and cost of ownership for financial decisions - Febrianto, Anggi; Suef, Mokh; Hakim, Muhammad Saiful (International Journal of Innovative Research and Scientific Studies, 2025)
The purpose of this paper is to develop a model for analyzing the heavy equipment business to support investment decisions through a new perspective of lifetime value and ownership cost. The research design of this study utilizes SEM-PLS (Structural Equation Modeling – Partial Least Squares) and develops a new model for heavy equipment investment analysis using mathematical modeling. This model is formed by combining several theoretical factors validated by practitioners in the heavy equipment field. The findings of this study indicate that all variables have a significant relationship with lifetime value and ownership cost. All variables also have a significant relationship with the feasibility study of the heavy equipment business. The practical implications of this research show a return on investment value of 93%, with a maximum profit value of 4,177 achieved at 8 years of age or 16,000 working hours. This model provides an illustration that heavy equipment reaches its most optimal value at a specific age when the predetermined variables are applied. The heavy equipment analysis model can serve as an assessment tool for the heavy equipment business.